PENGEMBANGAN BAHAN AJAR BERBASIS DISCOVERY APPROACH UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS IV SEKOLAH DASAR - Fatimah, Iis Daniati; Wiratama, Novialita Angga (Jurnal Tunas Pendidikan, 2023)
This research development is to develop teaching materials on the learning of Natural Science material nature and changes in The Shape of objects based on the discovery approach. The purpose of researchers to develop teaching materials based on the discovery approach to determine the validity and effectiveness of the developed teaching materials. This development is carried out using the ADDIE model which consists of 5 (five stage)namely analize (analysis), design (design), develop (development) implement (implementation),and evaluate (evaluation). Data analysis techniques used are data analysisvalidityand effectiveness data analysis. Based on the validation test, the results obtained that the teaching have very valid criteria for use with the percentage of material experts 76% , media experts 98% , and linguists 78%,product revisions have been made so that they can be tested subjects. Based on the test resultsto determine the effectiveness of learning outcomes obtained an average of 85.200 post test and pre test value of 76.600.